Case Report: Adequate T and B Cell Responses in a SARS-CoV-2 Infected Patient After Immune Checkpoint Inhibition - de Joode, K.; Oostvogels, A. A. M.; GeurtsvanKessel, C. H.; de Vries, R. D.; Mathijssen, R. H. J.; Debets, R.; van der Veldt, A. A. M. (Frontiers in Immunology, 2021)
After the COVID-19 outbreak, non-evidence based guidelines were published to advise clinicians on the adjustment of oncological treatment during this pandemic. As immune checkpoint inhibitors directly influence the immune system, concerns have arisen about the safety of immunotherapy during this pandemic. However, data on the immune response in patients treated with immunotherapy are still lacking. Here, we present the immune response in a SARS-CoV-2 infected patient who was treated with immune checkpoint inhibitors for advanced renal cell cancer. To evaluate the immune response in this SARS-CoV-2 infected patient, the number of T cells and their major subsets were measured according to expression of markers for co-signalling, maturation, and chemotaxis at baseline, during immunotherapy, and during the SARS-CoV-2 infection. In addition, plasma samples were analysed for IgM and IgG antibodies and the ability of these antibodies to neutralize SARS-CoV-2. Despite several risk factors for an impaired immune response to SARS-CoV-2, both T- and B-cell responses were observed. Even after treatment with immune checkpoint inhibitors, a sufficient cellular and humoral immune response can be achieved in a SARS-CoV-2 infected patient. These findings require renewed discussion on withholding of immune checkpoint inhibitors during the ongoing COVID-19 pandemic.